Long period oscillations in the longshore current on a sandy, barred coastinvestigated with Singular Spectrum Analysis - Zbigniew Pruszak (Oceanologia, 2005)
The presence of infragravity waves in nearshore regions can besought in the records of both water levels and wave-driven longshorecurrents. For this reason, time series of such currents in closeproximity to the shoreline were analysed using Singular SpectrumAnalysis (SSA). Simultaneously, the results obtained with thismethod were confronted with the output of Discrete Wavelet Transform(DWT), which had previously been applied to this data. The recordsof longshore currents were collected on a daily basis duringfield experiments in the autumns of 2002 and 2003 with samplingrates of 3 Hz and 0.5 Hz. This produced a large data set thatallowed for the use of an advanced signal processing technique,capable of extracting patterns characteristic of low-, medium-and high-frequency bands. It provided similar evidence to thatproduced by DWT for the existence of infragravity waves alonga dissipative coast with multiple bars. The study also demonstratedthe utility of SSA for studies on coastal hydrodynamics. It alsoshowed up the better user-friendliness of DWT in terms of patternextraction and interpretation. On the other hand, SSA demonstrateda higher precision of pattern extraction once the DWT outputwas known, which is a manifestation of the synergy of the twomethods when applied jointly.